Effects of different exercise modalities on oxygenation stress, inflammatory factors, and drug craving in drug users during the audit period - Chen, Yanmei; Wu, Shunjie (Quality in Sport, 2025)
Objective: To explore the effects of different exercise modalities on drug craving and the oxidative stress-inflammatory mechanisms in female addicts during rehabilitation. Methods: Forty female drug users were randomly assigned to yoga, meditation, physical fitness, or control groups (n=10 each). A 12-week intervention (3 sessions/week, 1 h/session) was conducted. Serum levels of malondialdehyde (MDA), homocysteine (HCY), tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6), IL-1, and intercellular adhesion molecule-1 (ICAM-1) were measured pre- and post-intervention. Drug craving was assessed via a visual analog scale (VAS). Results: (1) Female addicts exhibited elevated oxidative stress (MDA, HCY) and inflammatory markers (TNF-α, IL-6, IL-1, ICAM-1) compared to healthy individuals; (2) Post-intervention, these biomarkers significantly decreased in the yoga, meditation, and physical fitness groups (p<0.05); (3) VAS scores in all exercise groups showed marked reduction (p<0.01). Conclusion: Oxidative stress and inflammatory responses are present in female addicts during rehabilitation. Twelve weeks of exercise (yoga, meditation, or fitness training) effectively reduces these biomarkers, promotes inflammatory homeostasis, and alleviates drug craving, with comparable efficacy across modalities.